3D visualisation tool for improving the resilience to urban and coastal flooding in Torbay, UK. (2018) - Chen, Albert S.; Khoury, Mehdi; Vamvakeridou-Lyroudia, Lydia; Stewart, Dave; Wood, Mike; Savic, Dragan A.; Djordjevic, Slobodan
Abstract: Torbay, located in South West England, UK, is one of the Case Studies on the EU-funded project EU-CIRCLE, which is aimed at enhancing resilience of Critical Infrastructures (CI) to natural hazards. The region includes three urban centres (Torquay, Paignton and Brixham) and hosts more than 3 million tourists every year that contribute over £450 million to local economy. However, flooding, including coastal, fluvial and pluvial, has been a major threat to the area with more than 15 major incidents occurring since 1999. Rising sea levels, combined with increasing rainfall intensity, linked to climate change, are expected to exacerbate the problem. Better adaptation strategies are needed to safeguard CIs and services while improving resilience to climate hazards. EU-CIRCLE partners are engaged in a review of the existing capacity of flood defenses and the drainage systems in Torbay. To enhance the risk communication with the stakeholders, we adopted a high performance flood model to analyse the flood risk to Cis under a wide range of scenarios. The results are integrated into an innovative 3D visualization tool, showing the progress over time of any flood scenario in the region, via a fully interactive interface allowing stakeholders to better understand flood impacts to CIs.